Thermo-economic assessment of an externally fired hybrid CSP/biomass gas turbine and organic Rankine combined cycle - Pantaleo,AM; Camporeale,SM; Miliozzi,A; Russo,V; Mugnozza,GS; Markides,CN; Shah,N (Elsevier, 2017)
This paper focuses on the thermo-economic analysis of a hybrid solar-biomass CHP combined cycle composed by a 1.3-MW externally fired gas-turbine (EFGT) and a bottoming organic Rankine cycle (ORC) plant. The primary thermal energy input is provided by a hybrid concentrating solar power (CSP) collector-array coupled to a biomass boiler. The CSP collector-array is based on parabolic-trough concentrators (PTCs) with molten salts as the heat transfer fluid (HTF) upstream of a fluidized-bed furnace for direct biomass combustion. Thermal-energy storage (TES) with two molten-salt tanks (one cold and one hot) is considered, as a means to reducing the variations in the plant's operating conditions and increasing the plant's capacity factor. On the basis of the results of the thermodynamic simulations, upfront and operational costs assessments, and considering an Italian energy policy scenario, the global energy conversion efficiency and investment profitability are estimated for 2 different sizes of CSP arrays and biomass furnaces. The results indicate the low economic profitability of CSP in comparison to only biomass CHP, because of the high investment costs, which are not compensated by higher electricity sales revenues.